Does ICT based network competence mediate strategic competency’s impact on SMEs’competitve advantage? An empirical evidence from Malaysian manufacturing SMEs - Tehseen, Shehnaz *; Yafi, E.; Sajilan, Sulaiman; Rehman, H. U.; Butt, S. M. (Academy of Entrepreneurship, 2019)
Information and communication technologies (ICTs) have been considered as a strong mechanism for improving business growth and achieving competitive advantage. ICT based network competence is critical for developing and maintaining long-term relationships with customers, suppliers and other relevant parties. Assuming the mediating role of ICT based network competence, the main objective of this paper was to analyse the mediating effects of ICT based network competence in the relationship between strategic competency and firms’ competitive advantage in the context of Malaysian manufacturing SMEs. Survey strategy was used to collect data via standard structured questionnaire from 170 Malaysian entrepreneurs of manufacturing SMEs from Selangor and Kuala Lumpur. PLS-SEM technique was used for analysis of data. The study found a positive significant impact of strategic competency on competitive advantage, and also revealed a strong mediating influence of ICT based network competence on the relationship between strategic competency and competitive advantage.